Publisher Correction: Image Data Resource: a bioimage data integration and publication platform. (November 2018) - Williams, Eleanor; Moore, Josh; Li, Simon; Rustici, Gabriella; Tarkowska, Aleksandra; Chessel, Anatole; Leo, Simone; Antal, Bálint; Ferguson, Richard; Sarkans, Ugis; Brazma, Alvis; Carazo Salas, Rafael; et al.
This paper was originally published under standard Nature America Inc. copyright. As of the date of this correction, the Resource is available online as an open-access paper with a CC-BY license. No other part of the paper has been changed.